Proceedings of the 4th International Conference on Mobile Technology, Applications, and Systems and the 1st International Sympo 2007
DOI: 10.1145/1378063.1378067
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the mobile usage of e-lecture podcasts

Abstract: Distributing recorded classroom lectures via podcasting for replay on mobile devices is gaining increasing popularity. However, few insights exist regarding the actual usage and usefulness of such files, especially in situations where high-quality recordings of those lectures are available for non-mobile replay as well. In this paper, we compare the results of two surveys done with local students who had access to podcasts as well as high-quality files for replay on laptops and desktop PCs on the one hand and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 4 publications
2
17
0
3
Order By: Relevance
“…Therefore it is not surprising that less than 18% of the respondents who download OU resources from iTunes U do so because the materials are relevant to their studies. It also echoes the findings of Hürst, Welte & Jung (2007). Predictably, those respondents between ages 15-24 (the age bracket that most traditional university students fit into) have a bigger presence among those respondents who download because it is relevant to their studies than among those that download for personal or work reasons.…”
Section: How Do Users Engage With the Resources They Download?supporting
confidence: 67%
See 2 more Smart Citations
“…Therefore it is not surprising that less than 18% of the respondents who download OU resources from iTunes U do so because the materials are relevant to their studies. It also echoes the findings of Hürst, Welte & Jung (2007). Predictably, those respondents between ages 15-24 (the age bracket that most traditional university students fit into) have a bigger presence among those respondents who download because it is relevant to their studies than among those that download for personal or work reasons.…”
Section: How Do Users Engage With the Resources They Download?supporting
confidence: 67%
“…Is the iTunes U learner the same as the learners that took part in those studies? There is some evidence that the type of learner (either enrolled on a course or outside learner) has an effect on their use of podcast material, as found in (to this researcher's knowledge) the only paper available that compares 'internal' learners from a university with 'external' learners through iTunes U (Hürst, Welte & Jung, 2007). Hürst, Welte & Jung's research found that whereas internal learners fitted with the traditional university student age bracket, the age distribution of external users was more diverse, ranging from 17 to 53.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study [3] found a shift in the usage habits of students towards using the mobile version of e-lectures. Fig.…”
Section: Recordings Of Talks and Lecturesmentioning
confidence: 99%
“…A recent study [4] found a shift in the usage habits of students towards using the mobile version of e-lectures. The students used the mobile versions in different situations, e.g.…”
Section: Introductionmentioning
confidence: 99%